Effect of Profitability, Liquidity, and Dividends Per Share on Share Prices of Construction Companies Listed on The Indonesia Stock Exchange Period 2015 – 2019 - Harjuna, Zhammuel Nobel (Yayasan Ahmar Cendekia Indonesia, 2020)
The purpose of this research is to find out if the return of assets, current ratio, and dividends per share affects the Share Price. This research uses a quantitative approach. Sampling is done with purposive sampling techniques and selected as many as 9 companies that can be researched. The data in this study comes from secondary data obtained through IDX. The results of this study can be concluded that there is a significant influence between Return Of Assets, Current Ratio, and Dividends Per Share on the Share Price. In addition, hypothesis testing in this study used Multiple Linear Regression. The result of this study: the partial results show that Return On Assets (X1), Current Ratio (X2), Dividends Per Share (X3) have significant positive effect on the Share Price (Y).